Acute myeloid leukemia with oral manifestations: Case report and brief overview - Kruthika S Guttal; Venkatesh G Naikmasur; Krishna N Burde; Akhil C Deka (Wolters Kluwer Medknow Publications, 2008)
Many systemic diseases do manifest in the oral cavity. Leukemia is one such hematological disorder presenting with varied clinical and oral manifestations. Presented here is a case of gingival hyperplasia heralding the presence of acute myeloid leukemia and brief overview of the condition.